Blood in motion - Noordergraaf, Abraham; SpringerLink (Online service). (New York Springer, 2011)
Blood in Motion is a textbook in Cardiovascular Science. It sets out to introduce, entice and explain the cardiovascular system to the reader using a classical system in teaching: anatomy, physiology, general operation and specific systems. It is specifically designed to support the interests of students and experienced physiologists and clinicians. The book is subdivided into three parts which comprise a total of 11 chapters. Part I presents an historical perspective of cardiovascular knowledge and complements it with current insight into the physiology of the cardiovascular system. Part II explores sections of the circulatory loop, starting with an in-depth treatment of the veins, and including the lymphatic, the microcirculation, the arterial system and the heart. Part III incorporates approaches to the cardiovascular system as a whole, both in physiology and in science, such as modeling. This section introduces impedance-defined flow and offers the reader its application in mathematical modeling. At the end of each chapter, the reader will find questions designed to reinforce the information presented. Each chapter can be read or studied as an independent unit.
Part 1: Synoptic Reviews of Thinking in Circulatory Physiology -- Synoptic Reviews Of Cardiovascular Science From Different Approaches -- The Cardiovascular System and its Modes of Operation -- PART II: Circulatory Sub-Systems -- The Venous System -- The Heart -- Transmission of Arterial Signals, Venous Nonlinearity, and Body Movement -- The Microcirculation -- The Lymphatic System -- PART III: Impedence Defined Flow and the Closed Loop -- The Closed System -- Maintenance of the Circulation and Impedance-Defined Flow -- Circulatory Control -- Models of Cardiovascular Subsystems Yielding the Closed Circulatory Loop.-.
Electronic reproduction.
Keywords: Cardiovascular system -- Physiology; Cardiovascular system; Blood circulation; Electronic books